Introducing Family Tax Splitting in Germany: How Would It Affect the Income Distribution and Work Incentives? - Viktor Steiner; Katharina Wrohlich (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
We analyze the effects of three alternative proposals to reform the taxation of families relative to the current German system of joint taxation of couples and child allowances: a French-type family splitting and two full family splitting proposals. The empirical analysis of the effects of these proposals on the income distribution and on work incentives is based on a behavioral micro-simulation model which integrates an empirical household labor supply model into a detailed tax-benefit model based on the German Socio Economic Panel. Our simulation results show that under each reform the lion?s share of the reduction in taxes would accrue to families with children in the upper part of the income distribution, and that expected labor supply effects are small for all analyzed family tax splitting reforms, both in absolute terms and relative to the implied fiscal costs.
Keywords: H24; J22; H31; 330; Household Taxation; Income Distribution; Work Incentives; Microsimulation